2020
DOI: 10.1136/neurintsurg-2020-016194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thrombus surface on first pass reperfusion in contact aspiration and stent retriever thrombectomy

Abstract: BackgroundTo assess whether thrombus surface morphology has an impact on first pass reperfusion in contact aspiration (CA) and stent retriever (SR) thrombectomy.MethodsFrom January 2016 to December 2018, consecutive stroke patients with an occlusion of the middle cerebral artery and thrombectomy (CA or SR) were examined in this retrospective study. We assessed patients’ characteristics, procedural data and clinical outcome. Thrombus surface on pretreatment digital subtraction angiography (DSA) was categorized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Efforts to increase MT suc-K Fig. 4 First-pass expanded treatment in cerebral infarction (eTICI) distribution according to first-line SR-based retrieval technique for patients with acute anterior circulation stroke without susceptibility vessel sign cess by identifying imaging parameters that would allow prospective selection of the most effective retrieval technique for a specific clot are ongoing [2][3][4]. Bourcier et al [4] published the first study comparing MT techniques in AIS patients with SVS and concluded that first-line SRonly thrombectomy is superior to contact aspiration among those patients [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to increase MT suc-K Fig. 4 First-pass expanded treatment in cerebral infarction (eTICI) distribution according to first-line SR-based retrieval technique for patients with acute anterior circulation stroke without susceptibility vessel sign cess by identifying imaging parameters that would allow prospective selection of the most effective retrieval technique for a specific clot are ongoing [2][3][4]. Bourcier et al [4] published the first study comparing MT techniques in AIS patients with SVS and concluded that first-line SRonly thrombectomy is superior to contact aspiration among those patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, efforts to increase the chances of reperfusion after MT continue. Recent studies have focused on the identification of critical clot characteristics visible on imaging that might guide the choice of the best retrieval technique [2][3][4]. Due to the paramagnetic property of deoxygenated hemoglobin in trapped blood cells, susceptibility-weighted sequences can be used to locate thrombus material in occluded vessels after AIS, which may be seen as a distinct loss of signal within the affected vessel.…”
Section: Introductionmentioning
confidence: 99%
“…We found that a regular thrombus phenotype, cardioembolic stroke etiology, and occlusion in the middle segment of the BA might be predictors of complete recanalization if CA is chosen as the first-line thrombectomy method in BAO patients. However, phenotyping of the thrombus surface in BAO was technically less feasible compared to anterior circulation large vessel occlusions (acLVO) (9,18).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variants of the V4-segment of vertebral arteries (VA) were scored as described before (15). The readers independently categorized the proximal surface of the thrombus on the pretreatment DSA as "regular" if the profile was smoothly straight, convex, or concave (i.e., meniscoid-like) in the full vessel diameter, and "irregular" if these criteria were not met (Figure 1) (9). If readers were unable to determine the phenotype, we categorized the thrombus surface as not assessable and stated a reason.…”
Section: Occlusion Characteristics and Recanalization Statusmentioning
confidence: 99%
See 1 more Smart Citation